Penerapan Metode Musyafahah dan Metode Dril dalam Meningkatkan Hasil Belajar Tahsin Putri Kelas D2 Ltq Darul-Hikmah Bangkalan Ajaran - Mahmudah Mahmudah; Widia Qurrotaa'yun; Junaidi Junaidi (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Understanding tajwid material is an important aspect of learning the Qur'an. However, in practice, students often have difficulty understanding and applying tajwid rules correctly. Therefore, appropriate and effective learning methods are needed to help improve students' understanding. This study aims to improve the understanding of tajwid material in female students of class D2 at the Takhassusul Qur'an Darul Hikmah Institute through the application of the musyafahah method and the drill method. The musyafahah method emphasizes direct learning through examples of the teacher's reading that are imitated by students, while the drill method focuses on practice and repetition of material both inside and outside the classroom to strengthen students' mastery. This study used a classroom action research (CAR) approach with 17 female students in class D2 as research subjects. Data collection techniques included tests, observations, interviews, and questionnaires. The results showed that the application of the musyafahah and drill methods significantly improved students' understanding of tajwid material, as indicated by increased test scores and positive student responses to the learning process. Thus, it can be concluded that both methods are effective in improving students' understanding of tajwid material. Based on these findings, the study recommends that educators consider using the musyafahah and drill methods as alternative tajwid learning strategies to achieve more optimal learning outcomes.